PENERAPAN METODE CASEWORK DALAM MENGEMBANGKAN POTENSI REMAJA DARI KELUARGA EKONOMI TERBATAS : STUDI KASUS DI YAYASAN BAITUL MAAL BRILIAN RO MEDAN (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This research aims to understand the application of strength-based casework approach in developing the potential of adolescents from economically disadvantaged families. The study employed a qualitative case study method with a descriptive approach on a client with initials MZ, a 14-year-old male student in 8th grade from an underprivileged family in Medan Marelan. Data were collected through participant observation, in-depth interviews, documentation, and reflective notes during the period from March 3 to June 20, 2025, at Yayasan Baitul Maal BRILiaN RO Medan. Intervention was conducted through systematic casework stages including engagement, assessment, planning, intervention, evaluation, and termination using a strength-based approach. Evaluation using the CIPP model (Context, Input, Process, Product) showed positive results including increased client self-confidence from being shy to brave in showing work, improved self-expression from passive to actively discussing, enhanced family communication that is more open and mutually supportive, and increased motivation to continue education and create works. This research proves that parental support despite economic limitations can be an important factor in developing adolescent potential when combined with appropriate casework intervention.